Systematic review on the contents and parameters of self-management education programs in older adults with knee osteoarthritis - Kamsan, Siti Salwana; Singh, Devinder Kaur Ajit; Tan, Maw Pin; Kumar, Saravana (Blackwell Publishing, 2020)
Objective: The aim of this review was to determine the contents and parameters of self-management education programs (SMEPs) for older adults with knee osteoarthritis (KOA). Methods: A systematic electronic literature search (Scopus, MEDLINE, ProQuest, CINAHL, Cochrane and a grey literature specific site through Google Scholar) was undertaken between March and May 2018 (search updated in June 2019). Studies were selected based on predetermined criteria. Data relating to the contents and parameters of the SMEP were extracted and collated. Results: A total of 11 experimental studies met the inclusion criteria. Overall quality of the selected studies was good. The contents used for SMEP in older adults with KOA were information and management of KOA, healthy lifestyle and additional management strategies for KOA. The parameters used were face-to-face sessions led by health professionals and were chiefly group-based. Conclusion: This review comprehensively summarises the structure of multifaceted SMEP for people with KOA, which could be used to inform clinical practice and future research.